(untitled) (Conferencea, 2022)
This article talks about the achievements of the Bronze Age and the processes that took place in the Sughd oasis during the Early Iron Age. Based on historical data, the author studied and analyzed the unique aspects of the achievements of the Bronze Age and the processes that took place in the Sughd oasis in the early Iron Age based on the available scientific literature.